Synthesis and Characterisation of Monometallic Metal Oxide on Graphene Support: Electrocatalyst for Carbon Dioxide Conversion - Sharma, Kartik (My University, 2018)
Carbon dioxide is the major greenhouse gas and due to the reckless use and burning of fossil fuels by human beings its level is increasing in the atmosphere. As a result of which, it is causing problems like global warming to the planet. Therefore the increasing levels of carbon dioxide must be controlled or better reverted to avoid undesirable climate change. There are several ways to mitigate this problem of enhancement in carbon dioxide level. Among these, carbon dioxide capture and sequestration (CCS) is in use from last two decades. Carbon dioxide capturing can be done at three stages, Pre-combustion, oxyfuel combustion and post combustion. The drawbacks associated with this method are, high cost of CO2 capture and transport and lack of industrial commitments and incentives, it also damages the environment due to accidental leakage of CO2 from the pipelines or storage reservoir. CO2 utilization is another technique, in which atmospheric CO2 can be converted to useful chemicals and renewable fuels. This technique will not only reduce the CO2 level in atmosphere but also it will provide valuable products leaving behind the drawbacks associated with CCS technique. Many CO2 utilization techniques are popular, this includes the reduction of CO2 by chemical, photochemical, radiochemical and electrochemical methods. Different studies and experiments reveal that among them the process of electrochemical reduction is most promising and efficient method, because of its simplicity, small chemical intake and environment friendly nature. Due to the stable nature of CO2, it is often challenging to reduce it in different products. Other than this, there are some shortcomings like hydrogen evolution reactions (HER) and formation of multiple products that arise during the electroreduction process; therefore it is essential to get a suitable electrocatalyst which can produce the reduction products selectively with high faradic efficiency. Previous studies, reveals that Cu based electrocatalysts are most effective for CO2, electrochemical reduction process due to their excellent catalytic activity, high faradic efficiency and good stability. In the present work, synthesis of monometallic metal oxide (Cu2O) on graphene supported electrocatalyst has been done and these are further characterised with the help of suitable techniques like XPS, Raman spectroscopy and FESEM. On the basis of characterisation results, prepared catalyst was found suitable to be used as electrocatalyst for CO2 reduction to produce alcohols.
Master of Science- Chemistry
Keywords: CO2 electroreduction; Electrocatalysis; Fuel; Graphene; Graphene oxide